2006
DOI: 10.1152/ajpregu.00380.2005
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from an estivating frog: sparing muscle protein despite starvation and disuse

Abstract: Long (6- to 9-mo) bouts of estivation in green-striped burrowing frogs lead to 28% atrophy of cruralis oxidative fibers (P < 0.05) and some impairment of in vitro gastrocnemius endurance (P < 0.05) but no significant deficit in maximal twitch force production. These data suggest the preferential atrophy of oxidative fibers at a rate slower than, but comparable to, laboratory disuse models. We tested the hypothesis that the frog limits atrophy by modulating oxidative stress. We assayed various proteins at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 32 publications
3
48
0
1
Order By: Relevance
“…Previous studies have shown that aestivating C. alboguttata sustains hindlimb muscle mass until 6-9 months of aestivation (Hudson et al, 2006;Mantle et al, 2009). We suggest that decreased ROS production in 4 month aestivating skeletal muscle may represent a mechanism by which dormant C. alboguttata limit muscle fibre atrophy.…”
Section: Ros (H 2 O 2 ) Productionmentioning
confidence: 60%
See 2 more Smart Citations
“…Previous studies have shown that aestivating C. alboguttata sustains hindlimb muscle mass until 6-9 months of aestivation (Hudson et al, 2006;Mantle et al, 2009). We suggest that decreased ROS production in 4 month aestivating skeletal muscle may represent a mechanism by which dormant C. alboguttata limit muscle fibre atrophy.…”
Section: Ros (H 2 O 2 ) Productionmentioning
confidence: 60%
“…It has been shown that long periods of limb immobilisation stimulate increased ROS production in disused fibres (Min et al, 2011). Though many studies have investigated muscle antioxidant levels during dormancy and/or arousal in aestivators and hibernators (Ramos-Vasconcelos and Hermes-Lima, 2003;Hudson et al, 2006;Allan and Storey, 2012;James et al, 2013;Young et al, 2013), little is known about changes in mitochondrial ROS production and this has only recently received experimental attention in natural models of muscle disuse (Brown et al, 2012). Additionally, relatively few physiological studies examine mitochondrial function using permeabilised fibres, tissues or cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. alboguttata, 6-9 months of aestivation was reported to have no effect on muscle mass, water content or myofibre number in gastrocnemius or cruralis muscles (Mantle et al, 2009). Similarly, 6 months of aestivation had no effect on the total cross-sectional area of cruralis muscle (Hudson et al, 2006;Mantle et al, 2009). Furthermore, aestivation for 9 months in this species had no effect on myofibre cross-sectional area in the gastrocnemius, a key muscle involved in power output during locomotion (Mantle et al, 2009).…”
Section: Mechanisms Underpinning Inhibition Of Muscle Disuse Atrophymentioning
confidence: 90%
“…Consequently, the green-striped burrowing frog (C. alboguttata) has recently been used in our laboratory to study the effects of aestivation on skeletal muscle and bone, and the associated physiological and molecular processes that may confer resistance to musculoskeletal deterioration (Hudson et al, 2004(Hudson et al, , 2006Hudson and Franklin, 2002a;Mantle et al, 2009;Reilly et al, 2013;Symonds et al, 2007;Young et al, 2013). Prolonged inactivity associated with aestivation has been shown to have negligible effects on muscle mass, whole-muscle cross-sectional area, myofibre number, in vitro force production, bone-bending strength and swimming performance in C. alboguttata (Hudson et al, 2004(Hudson et al, , 2006Hudson and Franklin, 2002a;Mantle et al, 2009). The apparent absence of musculoskeletal losses in Cyclorana is consistent with the patterns reported for periods of disuse in hibernators as discussed above, and it is evident that the responses of muscle and bone to disuse in disparate organisms that undergo dormancy are profoundly different from those of typical models of disuse.…”
Section: Maintenance Of Musculoskeletal Properties In Hibernators Andmentioning
confidence: 99%